Chemical control of torpedograss - Weerasinghe, M.H.G. (My University, 1991)
In this research, a series of glasshouse and field trials were carried out to re-evaluate the chemical control of torpedograss (Panicum repens l.), with an intention to reduce the cost involved, either by improving the activity of the genera 11 y recommended he rb i c ide, glyphosate, with modified spray formulations, or by introducing new generation novel systemic 'graminicides', sethoxydim, f1uazifop-P or ha1oxyfop-methy1. G 1yphosate" sethoxydim, ha10xyfop-methy1 and f1uazifop-P applied as foliar sprays were evaluated for torpedograss control under both glasshouse and field conditions. In general, glyphosate and sethoxydim at the rates of 2.0 and 4.0 Kg/ha achieved superior control of the grass, suppress ing 90-95% regrowth 30 days after treatment and achieving 95-100% rhizome bud ki 11. The performance of f1uazifop and ha1oxyfop , as measured by regrowth suppression was significantly less at these rates, although the latter two herbicides also caused 90-95% kill of rhizome buds. Rates below 1.0 Kg/ha of all four herbicides gave insufficient regrowth suppression and bud ki11 and could not adequately cont ro 1 we 11 estab 1 i shed matu re plants. Of the herbicides tested ha10xyfop-methy1 showed the least phytotoxic effects on the grass. The effect of the quality of water used as the carrier volume had a significant effect on the performance of glyphosate. G1yphosate activity was enhanced greatly when de-ionized water was used instead of 'well' water to prepare the spray solutions, an effect attributable probably to the presence of cations in the 'well' water. Reduction in carrier volume from 600 L/ha to 300 L/ha did not alter the glyphosate activity significantly. The influence of several additives on glyphosate phytotoxicity was studied under glasshouse conditions. G1yphosate was 1ess phytotox i c when app 1i ed in 100 mM solution of calcium chloride and zinc sulphate, while the addition of magnesium sulphate or anmonium bicarbonate, did not alter glyphosate activity. Of the amonium salts added to the spray solutions, only ammoniumsulphate and urea at 0.5% enhanced the glyphosate activity. Non-ionic surfactants "AGRAL-90", and SURFACTANTN" both at 0.1% and 1.0% very significantly increased the performance of glyphosate, indicating that surfactant use should become a general recomnendation with glyphosate. A number of selected petroleum and vegetable oils used as adjuvants did not make significant alteration of glyphosate activity. When the pH of the spray solution was altered, glyphosate at pH 6 exhibited the best phytotoxic activity against the torpedograss.